Subject and Object Pronouns in High-Functioning Children With ASD of a Null-Subject Language - Terzi, Arhonto; Marinis, Theodoros; Zafeiri, Anthi; Francis, Konstantinos (Frontiers in Psychology, 2019)
Although the use of pronouns has been extensively investigated in children with autism spectrum disorders (ASD), most studies have focused on English, and no study to date has investigated the use of subject pronouns in null subject languages. The present study aims to fill this gap by investigating the use of subject and object pronouns in 5- to 8-year-old Greek-speaking high-functioning children with ASD compared to individually matched typically developing age and language controls. The ‘Frog where are you’ (Mayer, 1969) narrative task was used to elicit subject and object pronouns as well as DPs. Greek is a null subject language, and as a result, subject pronouns most often remain without phonological content. The results showed that both groups used more null than overt subject pronouns, indicating that children with ASD know that Greek is a null subject language. TD children used more null subjects than subject DPs, whereas children with ASD used an equal proportion of null subjects and subject DPs. In terms of object pronouns, both groups produced more clitics and object DPs than strong object pronouns, but the difference between clitics and DPs did not reach significance in either of the groups. Importantly, the groups did not differ from each other in the use of ambiguous pronouns in both the subject and object position. The ASD children’s avoidance to use pronominal subjects can be taken as evidence that they use a strategy to avoid infelicitous reference. This would suggest that the ASD children’s difficulties with pronouns is not due to difficulties in core grammar.